Symptom interpretation and health care seeking in ovarian cancer - Blaakaer Jan; Petersen Lone K; Seibaek Lene; Hounsgaard Lise (BMC, 2011)
Abstract Background Ovarian cancer is the leading cause of death among women suffering from gynaecological malignancies in the Western world. Worldwide, approximately 200,000 women are diagnosed with the disease each year. This article deals with the health care seeking and symptom interpretation process among Danish women, who have a very high mortality rate. Methods The health seeking and symptom interpretation process was analysed via combining study methods. The material consisted of registry data dealing with the use of public health care and hospital services of Danish women, newly diagnosed with ovarian cancer. These results were combined with findings from semi-structured qualitative research interviews on women's bodily experiences with symptom development. Results A number of 663 Danish women with ovarian cancer attended 27 different kinds of primary health care providers in a total of 14,009 visits during 2007. The women also had 6,214 contacts with various hospitals, and obtained 562 different diagnoses. From the main theme "Women's experiences with the onset of symptoms" three sub-themes were identified: "Bodily sensations", "From bodily sensation to symptom", and "Health seeking and treatment start". In all cases the General Practitioner represented the first contact to public health care, acting as gate-keeper to specialist and hospital referral. The women were major users of public health care throughout the diagnostic process and subsequent treatment. All women held personal knowledge concerning the onset of their symptoms. The early symptoms of ovarian cancer might be uncharacteristic and non-disease-specific when interpreted as personal experiences, but they had similarities when analysed together. Conclusions Diagnostic delay in ovarian cancer seems far from being exclusively a medical problem, as the delay proved to be influenced by organisational, cultural, and social factors, too. Initiatives facilitating the diagnostic process and research concerning the selection of individuals for further investigation are indicated. The way in which the women interpreted their symptoms was influenced by their personal experiences, their cultural, and their social background. This became crucial to the diagnostic process. These issues need to be explored through further research on women's experiences during the diagnostic process.